COX-2 Gene Promoter Polymorphism and Coronary Artery Disease in Middle-Aged Men: The Helsinki Sudden Death Study. (24th January 2008) - Huuskonen, KatiH.; Kunnas, TarjaA.; Tanner, MinnaM.; Mikkelsson, Jussi; Ilveskoski, Erkki; Karhunen, PekkaJ.; Nikkari, SeppoT.
Abstract : Cyclooxygenase (COX) catalyzes formation of prostaglandins that contribute to the inflammation in atherosclerosis. Our objective was to study whether the functional C variant of the− 765 G → C polymorphism in the human COX-2 gene associates with the severity of coronary atherosclerosis measured at the coronary artery level. The Helsinki sudden death study autopsy material ( n = 300) comprised of Finnish men who died suddenly. The area of atherosclerotic lesions in the coronary arteries was quantitated, and coronary narrowing was measured. The occurrence of myocardial infarction (MI) was assessed. Genotyping was by restriction endonuclease analysis. Men carrying the minor C allele had larger areas of complicated lesions ( P = .024) and a higher number of coronary arteries that had over 50% stenosis ( P = .036) compared to men representing the common GG genotype. The COX-2 polymorphism was not associated with MI. Our data suggest that COX-2 may be involved in plaque growth.